2020
DOI: 10.1021/acs.energyfuels.0c02158
|View full text |Cite
|
Sign up to set email alerts
|

Probing Aggregation Tendencies in Asphaltenes by Gel Permeation Chromatography. Part 2: Online Detection by Fourier Transform Ion Cyclotron Resonance Mass Spectrometry and Inductively Coupled Plasma Mass Spectrometry

Abstract: This work is the second installment of a study that probes the aggregation behavior of asphaltenes by gel permeation chromatography (GPC). In part 1, analysis of GPC aggregate fractions collected from the 2017 PetroPhase asphaltene sample by direct infusion revealed an inverse correlation between aggregate size and aromaticity. However, characterization of the largest aggregate fractions by direct infusion was hampered by solvent contaminant peaks and dynamic range limitations due to the extremely low ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 48 publications
4
35
0
Order By: Relevance
“…Collection of the GPC fractions (e.g., HMW and tailing), followed by solvent evaporation, dilution, and reinjection into the GPC separation system, yielded a nanoaggregate distribution similar to that obtained when the whole sample was injected (i.e., HMW and tailing). Moreover, we have used three GPC columns in series, which enables higher chromatographic resolution and observation of multimodal size profiles, compared to the monomodal-like distributions previously reported by Putman et al 69,79 The size distribution of the whole PetroPhase 2017 asphaltenes (black) indicates a diverse population of 51 Vcontaining aggregates. The integrated areas of the GPC chromatograms are presented in Table 1 and facilitate sample comparison.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collection of the GPC fractions (e.g., HMW and tailing), followed by solvent evaporation, dilution, and reinjection into the GPC separation system, yielded a nanoaggregate distribution similar to that obtained when the whole sample was injected (i.e., HMW and tailing). Moreover, we have used three GPC columns in series, which enables higher chromatographic resolution and observation of multimodal size profiles, compared to the monomodal-like distributions previously reported by Putman et al 69,79 The size distribution of the whole PetroPhase 2017 asphaltenes (black) indicates a diverse population of 51 Vcontaining aggregates. The integrated areas of the GPC chromatograms are presented in Table 1 and facilitate sample comparison.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Online molecular-level characterization has recently shown potential to mitigate the issues associated with fraction collection and off-line MS characterization. 69 There are few reports about petroleum analysis by chromatographic methods with online FT-ICR MS detection. 69,70 The reason is simple: close mass splits such as 3.4 mDa (species differing in SH 4 vs C 3 content) and 1.1 mDa ( 13 CH 3 32 S vs C 4 ), abundant in heavy petroleum and asphaltenes, are a challenge to resolve on a chromatographic time scale.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the predominance of island-type asphaltenes in DI-FT-ICR MS spectra was found to be caused by efficient ionization, or high monomer ion yield, whereas archipelago-type asphaltenes were revealed to poorly ionize due to a higher aggregation tendency [46,47]. Extrography fractionation of asphaltenes revealed that island and archipelago structural motifs are enriched in different solubility fractions, such as acetone (enriched in species with high monomer ion yield, island dominant) or tetrahydrofuran/methanol (enriched in species with low monomer ion yield, archipelago dominant).…”
Section: Introductionmentioning
confidence: 99%
“…Although FT-ICR MS only reveals molecular formulas, when coupled to gas-phase fragmentation such as IRMPD and collision-induced dissociation, it can supply useful structural information. However, all MS-based techniques are limited because of selective ionization, ion suppression, and matrix effects. Currently, there is not a “universal” ion source that allows for ionization of complex mixtures without any discrimination toward specific compound classes and structures. Therefore, prior sample fractionation is critical to achieving more complete molecular characterization of complex samples such as asphaltenes. …”
Section: Introductionmentioning
confidence: 99%